Perubahan Cadangan Karbon pada Peremajaan Karet Rakyat - Handi Supriadi; Yulius Ferry (Pusat Penelitian dan Pengembangan Perkebunan, 2014)
Rejuvenation of rubber tree (Hevea brasiliensis) can lead to a reduction of carbon stocks. Therefore, appropriate methods are needed to minimize such losses. The objective of this study was to analyze the changes on carbon stocks in the rejuvenation of rubber with logging system of 30%, 50%, 70%, and 100% and intercrops between the young rubber plantation (maize and peanuts). The research was conducted from January to December 2013 at smallholder rubber plantation in Way Tuba District, Way Kanan Regency, Lampung when the trees were 25 years old. The design used was a randomized block design with three replications. The tested treatments were logging of old rubber plants at 30%, 50%, 70%, and 100%, which then followed by planting of young rubber plants and intercropped (maize and peanut). The variables measured were: (1) fresh weight and dry weight (biomass); (2) fixed carbon content; and (3) carbon stocks on rubber plantation, maize, peanuts, and young rubber plants. The results showed that rubber logging at about 30%–100% could reduce carbon stocks by 7.4–24.29 ton C/ha. However, planting of young rubber plants as well as intercropped (maize and peanut) may contributed to the carbon enrichment up to 0.98-3.28 ton C/ha. Hence, the loss of carbon due to logging system turn out to be 6.29–22.92 ton C/ha.